2003
DOI: 10.1074/jbc.m309026200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Viscoelasticity of Human Cystic Fibrotic Sputum Correlates with Increasing Microheterogeneity in Particle Transport

Abstract: Current biochemical characterizations of cystic fibrosis (CF) sputum do not address the high degree of microheterogeneity in the rheological properties of the mucosal matrix and only provide bulk-average particle diffusion coefficients. The viscoelasticity of CF sputum greatly reduces the diffusion rates of colloidal particles, limiting the effectiveness of gene delivery to underlying lung cells. We determine diffusion coefficients of hundreds of individual amine-modified and carboxylated polystyrene particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
296
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(324 citation statements)
references
References 25 publications
(38 reference statements)
25
296
3
Order By: Relevance
“…Similarly, it may allow membrane vesicles exocytosed from the enterocyte brush border to bypass the mucin layer and enter the lumen [52]. The heterogeneous microrheological structure also has important consequences for the process of mixing within the intervillous space and our understanding of the transit and absorption of nanoparticles containing therapeutic substances that might adhere to viscoelastic regions [20,28,53]. While previous reports have indicated that mucins can accumulate in the intervillous space [18], the current work is the first to report the heterogeneous microrheology therein, its similarity to that around the villous tips suggesting that there is ongoing admixture and transit of these elements between the lumen and the intervillous spaces during longitudinal [54] and circular [55] contractile activity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it may allow membrane vesicles exocytosed from the enterocyte brush border to bypass the mucin layer and enter the lumen [52]. The heterogeneous microrheological structure also has important consequences for the process of mixing within the intervillous space and our understanding of the transit and absorption of nanoparticles containing therapeutic substances that might adhere to viscoelastic regions [20,28,53]. While previous reports have indicated that mucins can accumulate in the intervillous space [18], the current work is the first to report the heterogeneous microrheology therein, its similarity to that around the villous tips suggesting that there is ongoing admixture and transit of these elements between the lumen and the intervillous spaces during longitudinal [54] and circular [55] contractile activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have examined the microrheology [17][18][19]25 of mucins and mucus. Microrheology studies are particularly relevant to the transport of drugs and infectious agents such as bacteria and viruses across the mucus barrier.…”
Section: Introductionmentioning
confidence: 99%
“…NPs through the sputum of cystic fibrosis patients and relating the respected transport to the micro-viscosity and macro-viscosity characteristics of the sputum [44]. The group has also used MPT to quantify, for example, the intracellular transport of non-viral polyethyleneimine/DNA nano-sized polyplexes [45].…”
Section: Multiple Particle Trackingmentioning
confidence: 99%